Model Prediksi Financial Distress: Manakah yang Lebih Akurat dan Sesuai dengan Opini Auditor? - Fikri, Ahmad Faiz; Romadhon, Fitri; Akbar, Muhammad (Unversitas Islam Madura, 2024)
The financial performance of property and real estate sector companies has decreased significantly due to the covid-19 pandemic. The purpose of this study is to empirically test several financial distress prediction models in accordance with the initial auditor's opinion report and then compare them with the actual state of the company. The sample of this research is real estate companies listed on the Indonesia Stock Exchange from 2019 to 2020. The data analysis method in this research is to measure the accuracy, precision, and error rate of the Altman Z-Score, Ohlson, Fulmer, Grover, and Zmijewski prediction models. The results of this research show that the Grover model predicts financial distress most accurately, which is 70% for 2019 and 62% for 2020. Meanwhile, the Zmijewski model predicts financial distress with the highest level of conformity, which is 96% for 2019 and 86% for 2020.